The Filipino cancer patients' grief responses - Caronan, Marlyne B. 1973- (2001)
The incidence of cancer in the Philippines has risen to become the third's leading cause of morbidity and mortality. Many institutions, government and non-government organizations and different support groups, were organized and signified intentions in helping fight cancer.The thought of having cancer triggers an enormous grief response in a patient. As defined, grief is a dynamic process that changes in nature; it does not represent a rigid linear progression in emotions and thoughts as behavior but a continual move across different phases or stages. Being diagnosed with cancer does not only place that person to worry on its financial demands but more often than not, that person experiences psychological distress.Studies on grieving had been conducted in several areas, but most of these are foreign ones. Thus, this study was conducted to describe and analyze the grief responses of the Filipino cancer patients. It also studied the different coping strategies used by these patients, and touches on some variables such as socio-demographic factors, site of cancer, personality type, and support system which was thought to have an effect on the patients' grief responses.One hundred cancer-diagnosed patients participated in this study. Eighty participants came from the Cancer Institute of the Philippine General Hospital while twenty participants were patients outside the hospital. The study was conducted from August 15 to October 15, 2001. One on one interview technique was done using different tools, which comprise several questions to elicit the socio-demographic data, the personality type in the form of checklist, and interview schedule on the grief responses and coping strategies. The instruments underwent several pilot trials.The grief responses were divided into three phases namely the Initial Reaction, Following Initial Reaction, and Current Feelings or Acceptance. For the Initial Reaction, the grief responses were, felt sad, shocked, fear, cried, and asked God. The grief responses for the Following Initial Reactions were cried, felt sad, pitied self or family, asked God and fear of death. For the Current Feelings, most of the participants are happy while the rest are still sad, experiencing fear, and are still hopeful. Those who are happy are the ones who have already achieved acceptance.The coping strategies used by the participants during the Initial Reaction were praying, Bible reading, attending masses, visiting friends or relatives, making self busy with household chores, crying, just stayed home, and joined support groups for cancer patients.
For the Following Initial Reaction phase, the participants coped by visiting friends, attending religious activities, making self busy with work, stayed with the children, and by conditioning self free from illness. The coping strategies under Current Feelings were, keeping self busy with household chores, attending religious activities, just stayed home, attending support groups for cancer patients and visiting friends and relatives.The data were analyzed using descriptive statistics and correlation statistics such as the Chi-square at a present significance level of 0.05. The analysis yielded the following results.1. The older the persons, the more one can easily achieve acceptance or can cope with the illness.2. When one is optimistic, the acceptance and coping to illness can easily be achieved.3. Socio-demographic factors such as sex, religion, civil status, and occupation have no significant relationship to every phase of the grief response. Likewise, sociability and site of cancer are not also significantly related to every phase of the grief response.4. Support system is not significantly related to every phase of the grief response. However, qualitative analysis points out its great significance to patients with cancer.Based on the findings, grief response was indeed unique to every individual. Health professionals especially nurses and physicians have a great role to play in the care of patients with cancer. Interpersonal skills should be adequately developed especially during disclosure of the illness and during the grieving moments of the patients. Social support must be enhanced and maximized. This is important especially among Filipinos. Future researchers can make a similar study and explore on other factors that may influence grief response. In addition, grief responses can also be explored with other chronic illnesses. Lastly, study can be done to encourage future researchers to develop an instrument for measuring grief.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Cancer -- Psychological aspects; Grief